PERKEMBANGAN TEKNOLOGI DAN PENINGKATAN HASIL SAWAH PETANI DI KABUPATEN NGAWI JAWA TIMUR (STUDI KASUS DI KABUPATEN NGAWI JAWA TIMUR) - Larmintho, Rudy Bintoro Hari (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Indonesia's territory has changes and developments in land cultivation in terms of productivity and developments in micro or macro economic values. The setback of land cultivating workers in the fields now provides the best solution to procure harvesting machines. The concept of rural farmers has not been able to prioritize the advantages and disadvantages of harvesting by renting modern harvesting equipment. The main cause of this is that workers in rural areas do not have a livelihood such as harvesting and processing crops because they have been replaced by modern technology. The purpose of this research is to increase the productivity of food products and balance technology-based land processing. The approach used in this research is a qualitative case study design method. The main informants in this study were 3 village farmers and 1 village official in Ngawi district, East Java. The results of the study describe that the results of land processing and food for farmers in Indonesia are an important concern for the government to provide policies for providing sawan tools for farmers in Indonesia. The concern of the local government or the central government can reduce the cost of renting harvest processing technology with the hope that the economy of rural communities is stable and prosperous.